Carotid artery injury in endoscopic endonasal surgery: Risk factors, prevention, and management. Issue 1 (22nd March 2022) - Sharma, Rahul K.; Irace, Alexandria L.; Overdevest, Jonathan B.; Gudis, David A.
Abstract: Objective: Endoscopic approaches for sinus and skull base surgery are increasing in popularity. The objective of this narrative review is to characterize risk factors for internal carotid artery injury in endoscopic endonasal surgery (EES), highlight preventative measures, and illustrate key management principles. Data Sources: Comprehensive literature review. Methods: Relevant literature was reviewed using PubMed/MEDLINE. Results: Carotid artery injury in EES is rare, with most studies reporting an incidence below 0.1%. Anatomic aberrancies, wide dissection margins, as well as specific provider and hospital factors, may increase the risk of injury. Multidisciplinary teams, comprehensive preoperative imaging, patient risk assessment, and formal training in vascular emergencies may reduce the risk. Management protocols should emphasize proper visualization of the injury site, fluid replacement, rapid packing, angiography, and endovascular techniques to achieve hemostasis. Conclusions: While EES is a relatively safe procedure, carotid artery injury is a devastating complication that warrants full consideration in surgical planning. Important preventative measures include identifying patients with notable risk factors and obtaining preoperative imaging. Multidisciplinary teams and management protocols are ultimately necessary to reduce morbidity and mortality. Highlights: Internal carotid artery (ICA) injury is a rare complication of endoscopic endonasal surgery. Risk factors for ICA injury may include vascular anatomic variants, invasive pathology, and prior radiation therapy. Surgical team preparation and experience are key to successful management of operative complications.